Aplikasi Pemantauan Lokasi Keluarga berbasis Android - Malau, Emerson Porman; Sitanggang, Evita br (LPPM UNIKA Santo Thomas Medan, 2019)
High mobility by family members, makes it difficult for parents to supervise children's activities. At present supervision of children is not enough just to see or supervise directly. This application is designed to be able to monitor the location of the child's presence when parents want to know the whereabouts of their children. This application is also able to see the history of the existence of children in the time interval specified to be searched. This application is used android-based mobile devices. This application is expected to be used by parents to indirectly supervise their children's activities.